Social Entrepreneurship in Vocational Training: The Case of the Basque Country - Torres-Ortega, J (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2021)
Enterprises with social purposes or enterprises of the Social Economy have been viewed as an innovative, dynamic, inclusive and self-sustaining response to the main social, economic and environmental challenges facing our societies today. It is precisely by virtue of the relevant social and economic impact generated by business initiatives in the field of social entrepreneurship that supporting the emergence of social entrepreneurs has become a necessity, especially from an early age. Hence the importance of generating data that allows either creating or improving existing entrepreneurial training programs, which include specific training in social entrepreneurship among its objectives. In this line, the main objective of this research is to characterize and compare the students who participate in a training process in entrepreneurship aimed at young people between the ages of 16 and 24 taught at the Professional Training Centers of the Autonomous Community of the Basque Country, Spain. Specifically, it seeks to identify the main personal attributes related to the configuration of entrepreneurial intentions in these young people, as well as which of these traits are most related to intentions to undertake social endeavours, that is, the creation of organizations of the Social Economy. The information from this study was obtained by applying a survey to a sample of 5767 students belonging to different educational centers in the Basque Country. The results obtained reveal that potential entrepreneurs and non-entrepreneurs, as well as potential social entrepreneurs and potential commercial entrepreneurs, constitute quite homogeneous groups. However, the regression analysis revealed that there is a variable that significantly increases the probability of social entrepreneurship, which is precisely one of the factors that has been highlighted as a key characteristic of social entrepreneurship and Social Economy: solidarity.